Pemanfaatan Media Digital Canva pada Pembelajaran Bahasa Indonesia di Kelas X SMK - Anggun Cahyani; Hindun Hindun (Lembaga Pengembangan Kinerja Dosen, 2024)
This article aims to describe the use of Canva digital media in learning Indonesian for class X vocational school students. Media in learning is an intermediary in communication, assisting in conveying messages and information from the source of the message to the recipient of the message. The use and utilization of learning media does not only come from the work of one's own hands but can come from digital media such as today. Canva is a tool in digital media that can be used as a learning medium because it includes design and online visual communication that can be used by everyone in the world and can create and publish designs that have been created anywhere and at any time. The aim of this research is to find out to what extent students and educators have used Canva digital media and how effective it is in learning Indonesian in the classroom. The results of this research show that students and educators have used Canva as a medium for learning Indonesian, both in making PowerPoint for presentations, videos, posters, and infographics contained in the Canva feature. The technique used in this research is to observe and collect data from several students.